Finite Element Analysis of Acrylic Denture Produced From Visible Light Custom Tray - Nadira A Hatim; Ayad A Abdul-Razaq; Ibtehal H Al-Zubaidy (University of Mosul, College of Dentistry, 2009)
Aim: To determine stress analysis exerted by denture on the edentulous alveolar bone in the premolarregion represented by stone cast produced from visible light custom tray using linear finite elementmethod. Material and Method: Visible light custom tray (spaced and close fit) was used to producestone cast that represent the denture base and the underlying bone using silicone impression material.The dimension of the cross section of the stone cast was measured using Dimax program, then the datacollected was entering Excel program for making the figures. The dimension of the cross section of thestone cast entering finite element program and other new auxiliary program prepared specially for thisstudy for finite element analysis of vertical load of 100 Newton applied on the buccal cup (supportingcusp) of the second premolar tooth. Result: After the data was analyzed, the results were drawn infigures using surfer 7 program. High compressive, tensile, deflection, shear and maximum principalstress values were observed below the point of force application and in the underlying structure withdifferent values and locations according to the analysis in the mucous membrane and in the underlyingbone in the X and Y axes. Conclusion: By using finite element analysis, the more stress concentrationand deflection were found below the point of force application, in the mucous membrane, at the beginningof the cortical bone and along the buccal vestibule. The less stress concentration, deflection andless value of shear and maximum principle stress that distributed over large distance was found by usingvisible light cure spaced custom tray